Evaluation of Technology Literacy Capabilities Through Automotive Simulator Assisted Learning - Munawar, Wahid; Sriyono, Sriyono; Ramdhani, Ramdhani; Rajab, Ismadi (Fakultas Teknik Universitas Negeri Malang, 2022)
The purpose of the study was to assess student learning outcomes on automotive technology literacy skills in aspects of automotive technology knowledge and competence. The research method used descriptive method. The time of the study was carried out from January to March 2022. The research location is in the automotive study program vocational high school in Cimahi City. The research sample used cluster random sampling, 1 (one) class of 35 students was selected. The research instrument was a multiple-choice technological literacy test. Technological literacy indicators consist of identifying scientific problems, explain scientific phenomena, and using scientific evidence. The scope of the test questions is air conditioning in the vehicle. The test questions were validated by five automotive teachers and lecturers. Automotive learning treatment virtually and face to face, using simulator media. Data analysis using percentages. The results of the study show that 46.6 percent of students have automotive technology literacy skills in terms of knowledge and competence, 71 percent of students have scientific identification skills (car air conditioning issues), 46 percent of students have literacy using scientific evidence and 40 percent have literacy in explaining scientific phenomena